Motivasi Menonton Si Bolang di Trans7 dalam Mendorong Anak untuk Bermain Aktif - Hapsari Putri Utami; Sri Budi Lestari (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2020)
The 'opiate' case against gadgets makes children to put aside their active playing. One of the children's television shows which to date shows active playing is show cased in the Si Bolang program on Trans7. Preliminary observations by researcher found that 5 out of 7 children who watched Si Bolang liked the playing scenes that were displayed. The playing scene that was aired by Si Bolang showed activities that require a lot of body movements. The study entitled